Masticatory performance‐related factors in preschool children: establishing a method to assess masticatory performance in preschool children using colour‐changeable chewing gum. (16th September 2017) - Hama, Y.; Hosoda, A.; Komagamine, Y.; Gotoh, S.; Kubota, C.; Kanazawa, M.; Minakuchi, S.
Summary: A knowledge gap regarding masticatory performance in preschool children exists, which in turn delays intervention for preventive care; therefore, a method to easily assess performance is needed. The purpose of this study is to investigate the feasibility of assessing masticatory performance using colour‐changeable chewing gum and to investigate masticatory performance‐related factors in preschool children. This cross‐sectional survey was conducted in two childcare facilities and our laboratory. First, a one‐third quantity of colour‐changeable chewing gum was masticated by six adults to assess the nature and progression of colour changes in this quantity. Then, masticatory performance in 370 children 4–6 years of age was assessed using the same quantity of colour‐changeable chewing gum (60 chew strokes). The maximum bite force, body height, weight, age and number of healthy teeth were recorded. A t ‐test was performed to determine whether gum‐chewing experience or lack thereof produced a significant difference in masticatory performance. The Spearman's rank correlation coefficient was then determined for masticatory performance assessment values and other factors solely for children with gum‐chewing experience. Measurements from 259 children were obtained. Children with gum‐chewing experience demons trated significantly higher assessment values and were deemed to have been correctly assessed. A very weak but significant positive correlation was observed only between masticatory performance and the number of healthy teeth. The masticatory performance of preschool children was easily assessed using colour‐changeable chewing gum. The assessment values demonstrated significant correlation with the number of healthy teeth, but not with maximum bite force, body height, weight or age.